PENGGUNAAN PEMBELAJARAN KOOPERATIF TIPE TUTOR SEBAYA (PEER TUTORING) DALAM MENINGKATKAN KEAKTIFAN SISWA PADA MATA PELAJARAN MEKANIKA TEKNIK - Andreas Marco Gabriel (Jurnal Salome : Multidisipliner Keilmuan, 2024)
The teacher is a facilitator when class is in progress, but when learning is taking place the teacher is often ignored by students. Therefore, education will increasingly experience developments, especially in learning methods. With this article the author aims to add insight into educational innovation in peer tutoring learning methods. Peer tutoring is an active learning method that encourages students to learn well and can be a resource for other students. Peer tutoring can aim to increase student participation and development in Engineering mechanics subjects. So that teachers can have a reference for the character and communication found in each student. This article was created using a literature review method which combines information on research from each journal and articles for MEN in the Engineering mechanics subject and the use of peer tutoring methods in the Engineering mechanics subject.